2013
DOI: 10.1007/s11010-013-1826-0
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-α activation protects against endoplasmic reticulum stress-induced HepG2 cell apoptosis

Abstract: Live ischemia-reperfusion injury is associated with endoplasmic reticulum (ER) stress-induced apoptosis. Activation of peroxisome proliferator-activated receptor-α (PPARα) may inhibit hepatocyte apoptosis induced by oxidative stress and protect against liver injury. This study aimed to investigate the effects of PPARα activation, through a specific agonist, on ER stress-induced apoptosis in human liver hepatocellular carcinoma (HepG2) cells. HepG2 cells were challenged with H2O2 and treated with WY14643, a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In addition, MK886 has been shown to be a non-competitive inhibitor of PPARα activity. It inhibits PPARα activity though its impact on the transcriptional levels of PPARα promote-driven reporter31323334. In the current study, we found that MK886 negated NAMPT knockdown-induced ABCA1/G1 and LXRα expressions in these cells.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, MK886 has been shown to be a non-competitive inhibitor of PPARα activity. It inhibits PPARα activity though its impact on the transcriptional levels of PPARα promote-driven reporter31323334. In the current study, we found that MK886 negated NAMPT knockdown-induced ABCA1/G1 and LXRα expressions in these cells.…”
Section: Discussionsupporting
confidence: 56%
“…Exogenous FABP4 induces ER stress [30]. Activation of PPARα/γ could either promote or inhibit ER stress [3135]. We found that downregulation of HNF1b increased lipogenesis-related regulators and activated ER stress.…”
Section: Discussionmentioning
confidence: 85%
“…Curiously, however, there is a de-induction of BiP at the intermediate concentration of cpd_P, in association with the phenotypic shift toward terminal differentiation. A key mediator of cell death triggered by translational stress (i.e., downstream of BiP) is CHOP (CCAAT/enhancer-binding protein homologous protein, DNA damage inducible transcript 3 [39, 40]). Marked CHOP induction is observed at the higher concentrations of cpd_P in both the SUM159 and T98G cells.…”
Section: Resultsmentioning
confidence: 99%